Impact of a combined high cholesterol diet and high glucose environment on vasculature. - Zemin Wang; Yun Mao; Taixing Cui; Dongqi Tang; Xing Li Wang (PLoS ONE, 2013)
AIMS: Vascular complications are the leading cause of mortality and morbidity in patients with diabetes. However, proper animal models of diabetic vasculopathy that recapitulate the accelerated progression of vascular lesions in human are unavailable. In the present study, we developed a zebrafish model of diabetic vascular complications and the methodology for quantifying vascular lesion formation real-time in the living diabetic zebrafish. METHODS AND RESULTS: Wild type zebrafish (AB) and transgenic zebrafish lines of fli1:EGFP, lyz:EGFP, gata1:dsRed, double transgenic zebrafish of gata1:dsRed/fli1:EGFP were exposed to high cholesterol diet and 3% glucose (HCD-HG) for 10 days. The zebrafish model with HCD-HG treatment was characterized by significantly increased tissue levels of insulin, glucagon, glucose, total triglyceride and cholesterol. Confocal microscopic analysis further revealed that the diabetic larvae developed clearly thickened endothelial layers, distinct perivascular lipid depositions, substantial accumulations of inflammatory cells in the injured vasculature, and a decreased velocity of blood flow. Moreover, the vascular abnormalities were improved by the treatment of pioglitazone and metformin. CONCLUSION: A combination of high cholesterol diet and high glucose exposure induces a rapid onset of vascular complications in zebrafish similar to the early atherosclerotic vascular injuries in mammalian diabetic models, suggesting that zebrafish may be used as a novel animal model for diabetic vasculopathy.